2014
DOI: 10.1371/journal.pone.0116290
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting In Vitro Rumen VFA Production Using CNCPS Carbohydrate Fractions with Multiple Linear Models and Artificial Neural Networks

Abstract: The objectives of this trial were to develop multiple linear regression (MLR) models and three-layer Levenberg-Marquardt back propagation (BP3) neural network models using the Cornell Net Carbohydrate and Protein System (CNCPS) carbohydrate fractions as dietary variables for predicting in vitro rumen volatile fatty acid (VFA) production and further compare MLR and BP3 models. Two datasets were established for the trial, of which the first dataset containing 45 feed mixtures with concentrate/roughage ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Other researchers [ 63 66 ] identically demonstrated that the BP-ANN model had great abilities in information processing, high parallelism related to nonlinearity input variables, generalization, and the fault-tolerant capabilities as the nonparametric algorithm, which is widely used for classification, clustering, regression, and dimensionality reduction in several disease fields. The BP-ANN model was superior to linear regression because of its extraordinary processing ability for dealing with the hidden nonlinear relationship between input markers and the clinical outcome, which might be ignored by linear regression and statisticians [ 67 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers [ 63 66 ] identically demonstrated that the BP-ANN model had great abilities in information processing, high parallelism related to nonlinearity input variables, generalization, and the fault-tolerant capabilities as the nonparametric algorithm, which is widely used for classification, clustering, regression, and dimensionality reduction in several disease fields. The BP-ANN model was superior to linear regression because of its extraordinary processing ability for dealing with the hidden nonlinear relationship between input markers and the clinical outcome, which might be ignored by linear regression and statisticians [ 67 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…relationship between input markers and the clinical outcome, which might be ignored by linear regression and statisticians [67][68][69][70].…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…Subsequently, the NPA of the digestive precursors were assessed according to Loncke et al [21] and Martineau et al [28]. These models exhibited higher R 2 and lower standard deviation of the residuals compared with other published models of VFA production and absorption [65][66][67][68]. Nonetheless, regression-induced deviations, which over-or underestimate values in specific ranges of the data, have to be considered.…”
Section: Estimation Of the Supply With Glucogenic C In Cows During Ea...mentioning
confidence: 99%
“…GLUT1, which is a non-insulin Dairy 2022, 3 dependent glucose transporter on the apical and basal membrane of bovine mammary epithelial cells [112] is a major factor contributing to a constant rate of glucose uptake to the mammary glands of dairy cows. GLUT1 expression is regulated through local concentrations of growth hormone (GH) releasing factor and local hypoxia in response to the high metabolic activity of the mammary gland [68,113]. Therefore, the rate of glucose uptake to the bovine mammary gland remains fairly constant across a wide range of plasma glucose concentrations [114].…”
Section: Quantitative Glucose Metabolism Of the Mammary Glandmentioning
confidence: 99%